The Key Trends in Changes to Primary Education in the Czech Republic after the 1989 Velvet Revolution - Spilková, Vladimíra (Revija za elementarno izobraževanje, 2024)
The aim of the review study is to reflect on key trends in the process of transformation of primary education in the Czech Republic after the 1989 Velvet Revolution. The major milestones in the transformation process in terms of education policy are reflected upon. The core of the study is an analysis of the changes to primary education in the reality of school practice, including the most significant innovative approaches. The study concludes with an evaluation of the development of Czech primary education in the context of international trends and with reflection on the prospects for its further development.
Keywords: primary education, transformation, education policy